(untitled) (Journal of Vocational Innovation, Achievement and Education, 2025)
The availability of affordable and high-quality livestock feed remains a major challenge in the poultry sector, particularly for small- and medium-scale farmers. The high price of commercial feed has driven the need for alternative feed innovations that are more economical and environmentally friendly. One underutilized local raw material with significant potential is the sucker fish (Pterygoplichthys pardalis), which is abundant in Lake Tempe and often considered a pest. This study aims to analyze effective marketing strategies to increase sales of pellet feed made from sucker fish in Limpomajang Subdistrict, Marioriawa District, Soppeng Regency. This research employed a descriptive quantitative method, with data collected through interviews, observations, and questionnaires. Data analysis used the SWOT approach, supported by the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices to assess the strengths, weaknesses, opportunities, and threats in product marketing. The IFE score was 3.67, indicating strong internal advantages, particularly in good protein quality, affordable prices, and product availability. The EFE score was 2.48, suggesting considerable market opportunities despite threats such as competition from well-established commercial feeds and limited promotional reach. The combination of these values places the business in Quadrant I of the SWOT matrix (aggressive strategy), meaning its internal strengths can be leveraged to capture market opportunities. The optimal marketing strategy should focus on expanding distribution coverage, enhancing digital and educational promotion, and strengthening product branding to increase competitiveness in both local and regional markets.